Yeast Eukaryotic Initiation Factor 4B (eIF4B) Enhances Complex Assembly between eIF4A and eIF4G in Vivo - Park, Eun-Hee (American Society for Biochemistry and Molecular Biology, 2013)
Translation initiation factor eIF4F (eukaryotic initiation factor 4F), composed of eIF4E, eIF4G, and eIF4A, binds to the m(7)G cap structure of mRNA and stimulates recruitment of the 43S preinitiation complex and subsequent scanning to the initiation codon. The HEAT domain of eIF4G stabilizes the active conformation of eIF4A required for its RNA helicase activity. Mammalian eIF4B also stimulates eIF4A activity, but this function appears to be lacking in yeast, making it unclear how yeast eIF4B (yeIF4B/Tif3) stimulates translation. We identified Ts(−) mutations in the HEAT domains of yeast eIF4G1 and eIF4G2 that are suppressed by overexpressing either yeIF4B or eIF4A, whereas others are suppressed only by eIF4A overexpression. Importantly, suppression of HEAT domain substitutions by yeIF4B overexpression was correlated with the restoration of native eIF4A·eIF4G complexes in vivo, and the rescue of specific mutant eIF4A·eIF4G complexes by yeIF4B was reconstituted in vitro. Association of eIF4A with WT eIF4G in vivo also was enhanced by yeIF4B overexpression and was impaired in cells lacking yeIF4B. Furthermore, we detected native complexes containing eIF4G and yeIF4B but lacking eIF4A. These and other findings lead us to propose that yeIF4B acts in vivo to promote eIF4F assembly by enhancing a conformation of the HEAT domain of yeast eIF4G conducive for stable binding to eIF4A.